PENGARUH MOTIVASI DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA PEGAWAI DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MODERASI ( Studi pada Pegawai Dinas Pemberdayaan Perempuan dan Perlindungan Anak, Pengendalian Penduduk dan Keluarga Berencana Kabupaten - Laila Baroroh; Purbayu Budi Santosa; Muliawan Hamdani (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2017)
The purpose of this study is to examine and analyze the influence of motivation and professional competence on employee performance moderated organizational commitment to employees of the Department of Women Empowerment, Child Protection, Population Control and Family Planning Batang District. The population in this research is all employees of Department of Women Empowerment and Child Protection, Population Control and Family Planning Batang Regency which amounted to 113 people. The sampling technique used is the census method. The data were collected through questionnaires. Hypothesis testing in this research is done by multiple linear regression analysis. Based on the results of the study note that work motivation positive effect on employee performance. Professional competence has a positive effect on employee performance. Organizational commitment has a positive effect on employee performance. Organizational commitment moderates the influence of competence on employee performance. Organizational commitment moderates the influence of professional competence on employee performance.